Inhibition of ferroptosis alleviates high-power microwave-induced myocardial injury - Wang, Yu; Lu, Yan; Chen, Wen; Xie, Xiaohua (Frontiers in Cardiovascular Medicine, 2023)
Background:The use of high-power microwave (HPW) in our daily live is becoming more and more widespread, but the safety has also caused our concern. And ferroptosis is a newly discovered modality that can regulate cell death in recent years. The aim of our study was to demonstrate whether ferroptosis is an important cause of myocardial injury caused by HPW. And whether myocardial injury caused by HPW can be alleviated by inhibiting ferroptosis. Methods:We verified the extent of myocardial damage by different doses of HPW through in vivo and in vitro assays, respectively. In addition, GPX4 was knocked down and overexpressed in cardiacmyocytes to verify the altered sensitivity of cardiac myocytes to HPW. Finally, the therapeutic effect of Fer-1 and tanshinoneIIA on myocardial injury caused by HPW was verified in in vivo and in vitro assays. Results:We found that cardiac tissue and cardiomyocyte injury in mice gradually increased with increasing HPW dose, while ferroptosis markers were consistent with the injury trend. Gpx4 had an important role in ferroptosis in cardiomyocytes caused by HPW. Finally, tanshinoneIIA and Fer-1 could attenuate the damage of cardiac tissues and cardiomyocytes caused by HPW. Conclusions:In conclusion, our study found that ferroptosis, a novel mode of cell death, is present in myocardial injury caused by HPW. Moreover, tanshinone, a drug already in clinical use, can significantly reduce myocardial injury caused by HPW, which is promising to provide new therapeutic ideas for myocardial injury caused by HPW.